KARAKTERISTIK DEMOGRAFIS DAN KLINIS PASIEN HEPATITIS C DI RSUD TIPE C DI JAKARTA SELATAN: STUDI KOHORT BERBASIS DATA KLINIK - Muzakar, Cholid; Mustika P, Jeni; Priyatno, Teguh; Ari D, Ade (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
This study aims to analyze the demographic and clinical characteristics of Hepatitis C patients at a Type C Regional General Hospital in South Jakarta from 2021 to 2024. The data were extracted from medical records registered in the Hepatitis Information System (SIHEPI) of the Ministry of Health of the Republic of Indonesia. A cross-sectional design was used, with a total of 152 patients included. Results indicate that the majority of patients were aged 41–50 years (56.58%), and most were male (78.95%). Additionally, 32.24% of patients had HIV coinfections, while 51.97% had cirrhosis. The most common treatment regimen was a combination of sofosbuvir and daclatasvir, with 94.08% of patients completing the treatment. Among those who completed the treatment, 70.63% achieved a sustained virological response (SVR). This study provides an in-depth understanding of the local epidemiology of Hepatitis C in resource-limited settings, highlighting the need for enhanced screening and public health education to reduce coinfections and improve treatment outcomes. Penelitian ini bertujuan untuk menganalisis karakteristik demografis dan klinis pasien Hepatitis C di RSUD Tipe C, Jakarta Selatan, periode 2021–2024. Data diambil dari rekam medis yang tercatat dalam Sistem Informasi Hepatitis dan PISP (SIHEPI) Kementerian Kesehatan RI. Penelitian ini menggunakan desain cross-sectional dengan total 152 pasien. Hasil menunjukkan bahwa mayoritas pasien berusia 41-50 tahun (56,58%) dan berjenis kelamin laki-laki (78,95%). Sebanyak 32,24% pasien memiliki koinfeksi dengan HIV, dan 51,97% mengalami sirosis. Rejimen terapi yang paling umum adalah kombinasi sofosbuvir dan daclatasvir, dengan 94,08% pasien menyelesaikan terapi. Dari mereka yang menyelesaikan terapi, 70,63% dinyatakan sembuh (SVR). Penelitian ini memberikan gambaran epidemiologi lokal Hepatitis C di fasilitas kesehatan dengan keterbatasan sumber daya, sekaligus mengidentifikasi perlunya peningkatan skrining dan penyuluhan kesehatan untuk menurunkan angka kejadian koinfeksi dan meningkatkan keberhasilan pengobatan.